2021
DOI: 10.1016/j.idcr.2021.e01284
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines storm in COVID-19 with dengue co-infection in pregnancy: Fatal maternal and fetal outcome

Abstract: We report a 23-year-old pregnant woman who presented with acute high-grade fever, vomiting, and diarrhea for 5 days. She was first hospitalized in RSUD Tangerang—a secondary hospital based in Tangerang and were referred to Cipto Mangunkusumo General Hospital as a tertiary hospital. Initial laboratory results from previous hospital revealed leukopenia, low platelet, elevated aspartate transaminase, and alanine transaminase. Chest radiograph showed no pulmonary infiltration. Reverse transcriptase–PCR (RT-PCR) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, we were unable to conduct such investigations due to unavailability of tests. 7 Cross reactivity between the antibodies formed in both illnesses had been reported. 18 Hence, confirmatory diagnosis via RT-PCR for DENV would be ideal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we were unable to conduct such investigations due to unavailability of tests. 7 Cross reactivity between the antibodies formed in both illnesses had been reported. 18 Hence, confirmatory diagnosis via RT-PCR for DENV would be ideal.…”
Section: Discussionmentioning
confidence: 99%
“…Although DENV is endemic to south Asia, during this pandemic there is only one case of SARS-CoV-2/DENV co-infection reported in the literature. 7 We were able to identify four patients with SARS-CoV-2/DENV co-infection during the period from 1 st of April 2021 to 1 st of September 2021 in the De Soysa Hospital for Women in Colombo, Sri Lanka. We believe that it is timely to report this case series, which may aid to raise awareness and management.…”
Section: Introductionmentioning
confidence: 94%
“…Our findings were in alignment with other limited studies which have been published on this co-infection. Irwinda et al 5 reported a pregnant woman with this coinfection. Haemorrhagic manifestations were seen, and she succumbed to death due to multi organ failure, similar to what we had observed in our case 1 patient.…”
mentioning
confidence: 95%
“…Literature on its co-infection with COVID-19 during pregnancy is meagre. An increased risk of oligohydramnios, pre-term labour and maternal haemorrhage has been observed 5 .…”
mentioning
confidence: 99%
“… Study ID, Reference Type of Study Country Sample size Age Clinical Presentation Diagnosis of Dengue and COVID-19 Hospital stay and ICU Medication and treatment Maternal and Fetal outcome Mahajan NN et al, 2020 [4] Case Report India One 22 Primigravida, 37th week of gestational age, mild fever for 4 days, no petechiae, no bleeding tendencies, Hb: 12.7 g/dl; TLC:16800–12000, platelet count: 197000–343000/mm 3 Dengue NS1 Ag positive COVID-19 RT-PCR positive 9 days, No ICU admission Antibiotics, hydration therapy, no blood transfusion Mother: vaginal delivery through labor augmentation. Baby: PROMx2 days, IUGR fetus/ low birth weight (2.2 kg) Irwinda R et al, 2021 [5] Case Report Indonesia One 23 31 weeks of pregnancy, diagnosed as dengue shock syndrome with grade III dengue fever, multi-organ failure, Gravida 1 with 32 weeks of gestational age, Thrombocytopenia 17000/mm 3 ; IL-6: 18,812 pg/mL; IL-10: 1455 pg/mL; TNF-α: 18.11 pg/mL; IFN-γ: 5.5 pg/mL Dengue NS1 Ag and IgM positive COVID-19 RT-PCR positive in NPS 5 days, including ICU admission for ventilation Thrombocyte concentrate two packs Mother: death due to multiorgan dysfunction failure Foetus: intrauterine fetal death (IUFD) Schulte HL et al, 2021 [6] Retrospective study Brazil Two Platelets: 94000/mm 3 Retro-orbital pain, arthralgia, myalgia Dengue IgM positive, COVID-19 RT-PCR positive Yes, Two hospitalization Clinical improvement in 13 days. Hydroxychloroquine, Chloroquine, Enoxaparin, Azithromycin, Ceftriaxone Mother: gave birth without any complications Pregnancy gestational diabetes, chronic gastritis depression, platelets:196000/mm 3 , Fever, dry cough, myalgia, sore throat, nasal congestion, diarrhoea, anosmia, ageusia, and pruritus Dengue IgM positive, COVID-19 RT-PCR positive Yes, No ICU Analgesics, prednisone, hydration with 0.9% saline No pregnancy-related complications until 10th week of pregnancy Wijesinghe V et al, 2022 [7] Retrospective study Sri Lanka Four 24 …”
mentioning
confidence: 99%